PENGARUH FAKTOR FUNDAMENTAL DAN TEKNIKAL TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2009-2012) - Afrillian, Dhonny Yuartha; Rahardjo, Toto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine whether fundamental factors proxied by variables WCTO, ROE, DER, DPR, Sales Growth, and technical factors proxied by Beta affect firm value represented by PBV. The population in this research is a manufacturing company listed on the Indonesian Stock Exchange (BEI) in the period 2009-2012. Sampling methode using purposive sampling and acquired 36 companies were selected as sample. The analysis technique used is multiple regression, the classical assumption, hypothesis testing using t-statistics to test the partial regression coefficients and F-statistics to test the simultaneous effect on the level of significance of less than 5%, and Standardized Coefficients Beta Test to determine the independent variables that The most dominant effect on the dependent variable. The results of this research indicated that simultaneously (f-test), the average individual fundamental factors WCTO, ROE, DER, DPR, Sales Growth, and technical factors Beta affect the average PBV with R2 64.6%. Partial test (t-test)showed that the average ROE and Sales Growth has positive significant influence to the average PBV, while other average individual fundamentals factors WCTO, DER, DPR, and technical factors Beta did not influence the average PBV. Based on Standardized Coefficients Beta Test, the average ROE dominant influence the average PBV among other independent variables. Keywords: Working Capital Turn Over (WCTO), Debt Equity Ratio (DER), Return on Equty (ROE), Dividen Payout Ratio (DPR), Sales Growth dan Beta, serta Price of Book Value (PBV).